PRELIMINARY STUDY OF PYROLYSIS OF CACAO POD HUSKS AND PRODUCT YIELDS IDENTIFICATION - Mansur, Dieni (Teknologi Indonesia, 2014)
Pyrolysis of cacao pod husks as one of agricultural crop residue took place in a fixed bed type of pyrolyzer under atmospheric pressure at 500oC. The process was studied by varying methods and temperature of feeding.The effect of N2 flow rate as carrier gas was also investigated. These effects influenced yield of product after pyrolysis especially on the char. Char as the main product of pyrolysis was recovered as 70 C mol% with one step feeding at 25oC under 20 ml/min of N2. Pyrolysis of cacao pod husk also produced bio-oil that consisted of several chemical compounds such as aliphatic and cyclic ketones, carboxylic acids, furans, aldehydes, alcohols, phenols and heterocyclic aromatics.